The positive influence of Tibetan Buddhist monasteries on forest conservation - Shidong Zhang; Tong Wu; Luo Guo (Heritage Science)
Abstract The Qinghai-Tibetan Plateau (QTP) is vital for stabilizing climate in East and South Asia and its glaciers and snow meltwater nourish key continental rivers. The region’s forests are not only ecologically essential but also fragile. The practices of local herdsmen, shaped by long-standing cultural traditions, significantly affect forest dynamics. This study examines the vital role that Tibetan Buddhist monasteries play in forest conservation on the QTP. We utilize data sources including extensive field surveys and geospatial data to assess the impact of monastery and village locations on forest conditions. Spatial analysis techniques, such as Moran’s I and Ripley’s K function, reveal significant clustering of monasteries and villages, which are closely linked with forest conditions. Our findings indicate that forests near Buddhist monasteries have higher aboveground biomass and better quality compared to other areas, suggesting that their presence supports better forest conservation practices. This positive influence is attributed to the cultural significance of these sites and the environmental consciousness promoted by Buddhist cultural teachings. Additionally, this study employs analytical methods including Random Forest and Partial Least Squares Structural Equation Modeling (PLS-SEM) to explore the drivers of forest quality. Initial aboveground biomass, climatic factors, and monastery density emerge as key influences on forest quality within monastery buffer zones, indicating that cultural factors are crucial in shaping forest landscapes.